Factors Affecting Oral Participation in Lecturing Process in Prospective Accounting Teacher Students - Syah, M. Fahmi Johan; Huda, Syamsul; Budi, Hermawan Setyo (Dinamika Pendidikan, 2017)
The research aims to test the students’ engagement variable as intervening variable on the relationship between previous achievement and motivation to oral participation in accounting prospective teacher students at Muhammadiyah University of Surakarta. Besides, this research also tested whether attitudes affect oral participation directly. The population in this research is all students of accounting education at University of Muhammadiyah Surakarta (UMS), while the sample in this research was 300 samples. This research used path analysis test to identify direct, indirect, and total effect. The result of path analysis test showed that student engagement strengthens the relationship between previous achievement and motivation to oral participation in prospective accounting teacher students and attitude toward oral participation. Based on the result of research, it is needed  to improve the students’ oral participation, the previous achievement and motivation must be improved. Both of these factors will increase the students’ engagement that is happy feeling in the process of discussion, having dedication, and being able to overcome various problems.